1982
DOI: 10.1152/ajpheart.1982.242.6.h1077
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ischemia on mechanical function and high-energy phosphates in rabbit myocardium

Abstract: This study was designed to evaluate the effect of ischemia and reperfusion on myocardial mechanical function and high-energy phosphates in the neonate. All studies were performed utilizing the isolated arterially perfused septal preparation of newborn and adult rabbit hearts that were maintained at 27, 33, or 37 degrees C and paced at 90 beats/min. After mechanical function had been stabilized, 60 min of global ischemia was induced and was followed by 60 min of reperfusion. The muscle was kept in a humidified,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

1986
1986
1994
1994

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 0 publications
1
29
0
Order By: Relevance
“…These two variables are known to recover only very slowly after reversible ischemia, and some investigators (11,25,26,27,28) believe in a more than statistical relationship. Cumulative effects of repeated ischemia have been described (6).…”
Section: Discussionmentioning
confidence: 99%
“…These two variables are known to recover only very slowly after reversible ischemia, and some investigators (11,25,26,27,28) believe in a more than statistical relationship. Cumulative effects of repeated ischemia have been described (6).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to p-oxidation, activation of fatty acids with Coenzyme A (CoA) may continue for some time because the Km for ATP of the acylCoA synthetase reaction is comparatively low at 0.8mM [15]. Based on a cytosolic ATP concentration in normal myocardium of approximately 7 mM [16] and on reported rates of ATP depletion during no-flow ischemia [17,18], one would predict that fatty acid activation is not limited by lack of ATP for at least 30-60min. Indeed, myocardial accumulation of appreciable amounts of nonesterified fatty acids is a rather late phenomenon during ischemia starting after 20 to 30 min [15,19].…”
Section: Fatty Acid Metabolism During Acute Ischemiamentioning
confidence: 99%
“…These studies suggest that the ability of the myocardium to use anaerobic glycolytic path ways in order to maintain ATP levels and oth er cellular functions during hypoxia decreases with age. On the other hand, while numerous investigators have concluded that the new born heart is more tolerant of ischemia than the adult, others have found the opposite [5,6], Experiments performed on adult rat hearts show that decreases in coronary flow inhibit glycolysis [18] and suggest that the neonatal heart's adaptation is of major benefit only under hypoxic conditions where perfusion is adequate to remove the potentially toxic gly colytic products or when cooling limits their accumulation [19]. Questions concerning ap propriate methods for cooling the newborn heart to prevent ischemic injury have, how ever, recently re-emerged [12,13,20],…”
Section: Introductionmentioning
confidence: 97%
“…Age-related differences be tween the neonatal and the adult myocardium have been described, but the mechanisms causing the differences have not been eluci dated [3][4][5][6][7][8][9]. Partly for this reason, no consen sus has been reached on how medical treat ment should be designed to adjust for the agerelated differences [10,11], In particular, the effects of cold crystalloid cardioplegia (CCC) on immature myocardium remain controver sial [12,13].…”
Section: Introductionmentioning
confidence: 99%